Tensile properties of in-situ precipitated polydimethylsiloxane networks - Z. Zhang; Y-L. Yue; C. Zhang; H. Zhang; D-H. Zhang; X. Chen; Y-F. Chen (eXPRESS Polymer Letters)
Tensile propertiesof polydimethylsiloxane (PDMS) networks filled with in-situ precipitated silica were investigated. Experimental results showed that increasing the swelling time of cured rubber sheets in tetraethoxysilane (TEOS) solution or elevating the humidity and temperature of precipitation reaction atmosphere can render to a positive reinforcing effect. Moreover the in-situ precipitation method can be used to further enhance the tensile properties of fumed silica filled PDMS networks. The reinforcement introduced by the in-situ precipitated silica gel particles can probably be attributed to the adsorption of polymer chains onto silica surface, the pinning effect of polymer chains within gel particles, and the fillerfiller gel structure among gel particles.